The Advantages of Combined Regional and General Anesthesia in Ophthalmic Surgery in Children - Abdul-Sattar, Rand S.; Al-Maini, Ali H. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Regional anesthesia is a common procedure in an adult patient undergoing ophthalmic surgery but it cannot be done alone in the pediatric age group. General anesthesia is accompanied by complications intra- and post-operatively. Objectives: to determine whether or not using regional anesthesia in combination with general anesthesia in pediatric eye procedures improves patient outcomes. Methods: Forty children, with an age range of 6 - 12 years were included in the study that was conducted at Ghazi Al-Hariri Hospital / Department of Ophthalmology and Ibn Al-Haytham (Ophthalmology Hospital), both teaching hospitals, from December 2018 to October 2019. These children were allocated into two groups: GA (general anesthesia), and GA-R (general anesthesia-regional anesthesia). Heart rates, mean arterial blood pressure, oculo-cardiac reaction, and postoperative nausea and vomiting were measured. All required approvals were obtained from the scientific committee of the Iraqi Board for Medical Specializations. Statistical analysis was done using SPSS V26, with a P value of <0.05 considered significant. Results: None of the patients developed oculo-cardiac reactions or needed additives to the anesthesia given during surgery in the GA-R compared to the GA group. Intra-operative measurements of heart rates and mean arterial blood pressure were lower in the GA group than in the GA-R group (p<0.05). In comparison to the GA group, the GA-R group had a lower incidence of postoperative nausea and vomiting (p<0.05). A greater number of patients in the GA group needed analgesia than in the GA-R group. Conclusion: The use of regional anesthesia as a peribulbar block with general anesthesia is a safe and successful procedure in pediatric ocular surgeries.